Inaperturate Pollen in Monocotyledons - Furness, Carol A.; Rudall, Paula J. (International journal of plant sciences, 1999)
Inaperturate pollen is widespread in the monocotyledons, includes a diverse range of forms, and has arisen independently numerous times. Evidence for this comes from the phylogenetic distribution of inaperturate pollen and also from developmental and structural differences. There is no correlation between the production of inaperturate grains and either microsporogenesis type or tapetum type. Inaperturate pollen has phylogenetic significance within some groups, e.g., in Zingiberales, Liliales, and some Asparagales. Character states for inaperturate pollen are presented. It can broadly be divided into two types, “omniaperturate” and “functionally monoaperturate,” based on the thickening of the intine. The characters of omniaperturate pollen are adaptations that potentially increase the germination efficiency of the pollen. Both types sometimes occur in environments where pollen is not subject to desiccation and, thus, may remain viable with reduced exines.